Pi-Security: An IOT Based Home Security System - Deepak Mangal, Asheesh Tiwari, Saurabh Singhal (International Journal of Advanced Science and Technology, 2020)
Connecting the devices through the Internet and monitoring them over remotely is the idea of Things (IoT). When it comes to home security, the concept of IoT can be incorporated to make home a better place to live by making it safer, automated and smarter. Pi-Security is an IOT based Home Security System, which is developed in order to inculcate the features of a high-end home security system, and still be affordable enough to fit in the budget of an Indian common man. This project focuses on sending alerts to the user’s smartphones when an unknowing case occurs by using internet services. Besides this, the sensors can be used to make home automated. Also, sensors are used to detect any gas leak in the home and alert the owner about the same. Keywords: PIR, IR, Finger Print Sensor, Pi-security, Node MCU, Internet of Things, Raspberry Pi.